Association between triglyceride glucose-waist height ratio and stroke: a population-based study - Xu, Fangyuan; Su, Xingxing; Dai, Fan; Ye, Yu; Hu, Peijia; Cheng, Hongliang (Frontiers in Endocrinology, 2025)
BackgroundStroke poses a substantial threat to global public health. The triglyceride glucose-waist height ratio (TyG-WHtR), which incorporates the TyG metric with obesity-related WHtR, has demonstrated superior diagnostic and predictive value compared to the TyG index alone. Nevertheless, there is still a lack of in-depth exploration into the relationship between TyG-WHtR and stroke. This study seeks to address this gap by extracting information from the National Health and Nutrition Examination Survey (NHANES) to elucidate the potential association between TyG-WHtR levels and stroke.MethodsThis study included 8,757 individuals from four research cycles conducted between 2011 and 2018. To examine the potential relationship between TyG-WHtR and stroke, we conducted multivariable logistic regression analysis. In addition, smooth curve fitting was applied to display the nonlinear association. Subgroup analyses and sensitivity analyses contributed to examining the robustness and consistency of the relationship between TyG-WHtR and stroke. The receiver operating characteristic (ROC) curves were employed to evaluate the diagnostic capability of TyG-WHtR and TyG.ResultsAfter adjusting for relevant covariates, a positive association between TyG-WHtR levels and stroke occurrence was observed (OR: 1.26, 95% CI: 1.02-1.55). Specifically, each unit increase in TyG-WHtR was associated with a 26% higher likelihood of stroke. The findings of sensitivity analysis further demonstrated the stability of this positive relationship. Subgroup analysis revealed that this association was significant among participants who did not engage in moderate exercise and those without coronary heart disease or angina pectoris. ROC analysis demonstrated that TyG-WHtR exhibited superior predictive value compared to TyG.ConclusionThis study identified an association between elevated TyG-WHtR levels and an increased prevalence of stroke, suggesting that TyG-WHtR may serve as a valuable predictive tool for stroke risk, with potential implications for clinical prevention and early intervention.